Human Capital Development in Science,Technology and Mathematics Education: Implications for Sustainable Development in Africa - Daso, Peter Ojimba (Mediterranean Journal of Social Sciences, 2012)
This paper harped on human capital development in science, technology and mathematics education withspecial reference to its implications for sustainable development in Africa. The usefulness and relevance ofscience, technology and mathematics education to sustainable development in African Nations are nolonger in doubt. Therefore any nation that plays with these indices plays with her own development.America is a super power today because she has been able to transfer her science into technology. Thiscould also be done in Africa through effective and efficient development of STM human capital. This paperdiscussed the rational for human capital development in STM education, the economic implications ofhuman capital development in STM education and the attendant suggestions to improve human capitaldevelopment in the STM programme in Africa.